Factors of the term structure of sovereign yield spreads and the effect on the uncovered interest rate parity model for exchange rate prediction - Reddy, Desigan (Department of Finance and Tax, 2019)
Using a Principal Component Analysis (PCA) approach, we investigate the sovereign yield spread term structure of the BRICS economies against the U.S. We show that the term structure for these markets are primarily driven by three latent factors which can be classified as the spread level, slope and curvature factors. We further postulate that a country’s yield curve contains valuable information about its future economic state and as such the PCA derived spread factors, which are based on the differences between sovereign yield curves, encapsulates material macro-economic information between the countries. In light of this, we show that augmenting the traditional Uncovered Interest Rate Parity model (UIRP) with these factors improves the models predictive accuracy of exchange rate movements.